투시장비를 이용한 중재 시술 중 의료 방사선 중재 시술자의 방사선 노출 최소화를 위한 권고안 - 신일상; Il Sang Shin; 이윤나; Yun Nah Lee; 이준규; Jun Kyu Lee; 김주성; Joo Seong Kim; 김승범; Sung Bum Kim; 금지영; Jiyoung Keum; et al. (The Korean journal of gastroenterology, 2024)
As fluoroscopy-guided interventional procedures gain popularity, the associated health threats from radiation exposure to intervention-alists during these procedures are increasing. Therefore, an understanding of the potential risks of radiation and careful consideration on minimizing exposure to radiation during the procedures are of paramount importance. The Korean Pancreatobiliary Association has developed a clinical practice guideline to minimize radiation exposure during fluoroscopy-guided interventional procedures. This guideline provides recommendations to deal with the risk of radiation exposure to interventionalists who perform fluoroscopy-guided procedures, and emphasizes the importance of proper and practical approaches to avoid unnecessary radiation exposure. (Korean J Gastroenterol 2024;84:251-264)